Proceedings of the 38th International Symposium on Multiparticle Dynamics (ISMD08) - Bartels, J; Borras, K; Gustafson, G; Jung, H; Kutak, K; Levonian, S; Mnich, J; Achilli, A; Albacete, J; Albrow, MG; Alvarez-Gaumé, L; Ambroglini, F; et al. (2009)
Proceedings of ISMD08